2007
DOI: 10.1080/09513590701584931
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of progestins on bone quality and fractures

Abstract: The effects of progestins on the quality of bone and their influence on the risk of fractures are reviewed. Data discussed are based on experimental studies in vivo that generally lasted for longer than one year. Information is given on the background of osteoporosis and on several means of inducing changes in bone quality. In young women who start using oral contraceptives based on progestins alone shortly after pubertal development, a significant decrease in bone quality has been documented. World Health Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The benefits include, reduction of heavy menstrual bleeding due to the high incidence of amenorrhea after longer use, a reduced risk of pelvic inflammatory disease, reduction of endometriotic pain, fewer painful crisis in women with sickle cell disease and reduction in vasomotor symptoms [ 20 ].…”
Section: Health Risks and Benefitsmentioning
confidence: 99%
“…The benefits include, reduction of heavy menstrual bleeding due to the high incidence of amenorrhea after longer use, a reduced risk of pelvic inflammatory disease, reduction of endometriotic pain, fewer painful crisis in women with sickle cell disease and reduction in vasomotor symptoms [ 20 ].…”
Section: Health Risks and Benefitsmentioning
confidence: 99%
“…In 2007, Thijssen [44] concluded in a review that among adolescents (menarche to 518 years), the advantages of using progestin-only contraceptives outweigh the theoretical safety concerns regarding fracture risk. The WHO statement concludes that there should be no restriction on the use of progestin-only contraceptive methods among women who are otherwise eligible to use these methods.…”
Section: Progestin-only Oral Contraceptivesmentioning
confidence: 99%
“…36 Although a few early clinical studies suggested that there may be some beneficial effects of progesterone and progestins on bone, 37 more recent clinical trials do not provide evidence that progesterone or ''pure'' (PR-selective) progestins improve bone density in postmenopausal, hysterectormized, or amenorrheic women. 38 The role of androgen receptor (AR)-mediated effects of androgenic progestins (eg, NETA, tibolone, levonorgestrel, etc) on bone in women remains unclear. In mice, loss of the AR results in bone loss in males but not females.…”
Section: Pharmacologic Basis Of Add-back Therapy: Role Of Estrogen and Progesteronementioning
confidence: 99%